2013
DOI: 10.3171/2013.1.jns121370
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular schwannomas in the modern era: epidemiology, treatment trends, and disparities in management

Abstract: Object There are a variety of treatment options for the management of vestibular schwannomas (VSs), including microsurgical resection, radiotherapy, and observation. Although the choice of treatment is dependent on various patient factors, physician bias has been shown to significantly affect treatment choice for VS. In this study the authors describe the current epidemiology of VS and treatment trends in the US in the modern era. They also illustrate patient and tumor characteristics and elucidate their effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
161
1
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(180 citation statements)
references
References 59 publications
11
161
1
7
Order By: Relevance
“…3,21 The present study extends our patient series and the length of follow-up from our previous report. 20 We analyzed the outcomes of GK SRS for VS patients who had recurrent or residual tumors after 1 or more previous resections.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…3,21 The present study extends our patient series and the length of follow-up from our previous report. 20 We analyzed the outcomes of GK SRS for VS patients who had recurrent or residual tumors after 1 or more previous resections.…”
supporting
confidence: 69%
“…The incidence of VS is estimated to be 1 per 100,000 individuals per year, and it accounts for approximately 8% of all intracranial tumors in adults. 3,14 These tumors are typically slow growing (0-3.9 mm per year), but without management, most VS tumors will grow within 3 years. 4,6,14,15,18,20 For many years, microsurgical resection remained the most commonly recommended treatment for patients with newly diagnosed unilateral VS. 3,20 Although surgical outcomes have improved over the last 30 years, resection of VS was frequently associated with impaired facial nerve function and loss of hearing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from studies prior to 2004 likely underestimated the true incidence of vestibular schwannomas since collection of data on non-malignant brain tumors was not mandatory prior to the Benign Brain Tumor Act in 2004. Populationbased studies published after 2004 demonstrate a similar incidence [9,10]. To date, prior studies on the populationbased incidence of vestibular schwannomas in the US collected data from either a single county or national databases covering a maximum of 28 % of the US population [8][9][10].…”
Section: Study Interpretationmentioning
confidence: 97%
“…Watchful waiting and radiotherapy are widely accepted in the management of vestibular schwannomas, a tumor that is usually indolent but, like HNPG, also has an unpredictable growth pattern. Review of different national tumor registry databases revealed that in the United States there has been a significant shift in management of vestibular schwannomas over a decade, with increasing tendency toward observation and radiotherapy, whereas the proportion of operated cases declined to near a half of the total [1][2][3]. Similar studies on the trends of treatment are lacking in HNPG.…”
mentioning
confidence: 92%